Identity as a psychological compass: the mediating role of resilience in international students’ college adjustment amidst culture shock - Yang, Weimin; Gao, Lili (Frontiers in Psychology, 2025)
IntroductionThe rapid increase in international students in China underscores the imperative to understand their successful adaptation. This study investigates the roles of identity and psychological resilience in facilitating college adjustment among international students confronting culture shock in China.MethodsDrawing upon Social Identity Theory and Identity Consolidation Theory, we hypothesized that a strong sense of identity would positively influence psychological resilience, mediating the relationship between identity and college adjustment. A quantitative survey was conducted with 2,097 international students in various universities across China.ResultsThe findings indicate that identity significantly predicted higher levels of psychological resilience, and psychological resilience, in turn, was a strong predictor of better college adjustment. Furthermore, psychological resilience significantly mediates the relationship between identity and college adjustment, suggesting that a well-defined identity contributes to resilience, equipping students to navigate the challenges of culture shock and adapt successfully to university life.DiscussionThese results provide valuable insights for developing targeted support programs and interventions to enhance international students’ well-being and successful integration in China.